Penerapan Model Problem Based Learning pada Materi Transformasi Geometri untuk Meningkatkan Hasil Belajar Siswa - Iqbal, Muhammad Iqbal Zuwandi; Amrullah; Ketut Wartane; Gunawan (FKIP Universitas Mataram, 2025)
This research aims to improve student learning outcomes through the application of problem-based learning models on geometric transformation materials (rotation and dilation). This type of research is a class-action-research (PTK) that looks at student development in 2 cycles. Data collection techniques were carried out using formative tests. Data analysis used in this study using descriptive statistical analysis. The application of PBL learning model on geometry transformation material (rotation and dilation) gives good results. The data obtained from the research conducted are as follows: (1) In cycle 1 the percentage of students' classical completeness reached 62% with an average score of 79.45. The results in cycle 1 have not met the minimum classical completeness criteria of 80%. (2) In cycle 2, there was an increase both in terms of the percentage of classical completeness and the average score. The number of students who completed this cycle was 82% with an average score of 84.08. This indicates that the research by applying PBL model on geometry transformation material is successful.